Presupposition Accommodation of the German Additive Particle auch (= “too”) - Grubic, Mira; Wierzba, Marta (Frontiers in Communication, 2019)
Presupposition triggers differ with respect to whether their presupposition is easily accommodatable. The presupposition of focus-sensitive additive particles like also or too is often classified as hard to accommodate, i.e. these triggers are infelicitous if their presupposition is not entailed by the immediate linguistic or non-linguistic context. We tested two competing accounts for the German additive particle auch concerning this requirement: First, that it requires a focus alternative to the whole proposition to be salient, and second, that it merely requires an alternative to the focused constituent (e.g. an individual) to be salient. We conducted two experiments involving felicity judgments as well as questions asking for the truth of the presupposition to be accommodated. Our results suggest that the latter account is too weak: mere previous mention of a potential alternative to the focused constituent is not enough to license the use of auch. However, our results also suggest that the former account is too strong: when an alternative of the focused constituent is prementioned and certain other accommodation-enhancing factors are present, the context does not have to entail the presupposed proposition. We tested the following two potentially accommodation-enhancing factors: First, whether the discourse can be construed to be from the perspective of the individual that the presupposition is about, and second, whether the presupposition is needed to establish coherence between the host sentence of the additive particle and the preceding context. The factor coherence was found to play a significant role. Our results thus corroborate the results of other researchers showing that discourse participants go to great lengths in order to identify a potential presupposition to accommodate, and we contribute to these results by showing that coherence is one of the factors that enhance accommodation.